Effect of stretcher height on rowing technique - Kleshnev, V. (BioRow, 2020)
The results of the study indicate that lower stretcher position could be beneficial for rowing power and technique. The obtained data has proved usability and accuracy of the new BioRow stretcher force sensor which has been developed recently in BioRow. It consists of four load cells measuring only the horizontal force component at the toes-heels/ left-right foot (Fig.1). With specific attachments, the sensor can be used in any boat or rowing machine. A 2D version is available to measure both horizontal and vertical force components.